Yahoo Web Search

  1. Sort by

  1. These things are fun: LHS = cotx + tanx = [cosx / sinx] + [sinx / cosx] = [cos² x + sin² x] / [sinx...

    1 Answers · Education & Reference · 17/10/2012

  2. LHS = (sec x-csc x)./ (sec x csc x) = (1/cosx) - (1/sinx) / [(1/cosx)(1/sinx)] = [(sinx...1] [because to divide by a fraction invert and multiply] = sinx - cosx = RHS LHS = (sin x + cos x)/ cos x - (sin x- cos x)/ sin x = [sinx(sinx + cosx) - cosx(sinx - cosx...

    1 Answers · Education & Reference · 11/01/2010

  3. [LHS - left side of '='. RHS - right side of '='] 1] LHS: multiply... by 60. The result is the value of P. 2] same procedure for LHS & RHS. Divide both sides by 13 to get the value of E...

    4 Answers · Education & Reference · 10/01/2007

  4. LHS=sec^4 x-tan^4 x =(sec^2 x +tan^2 x) (sec^2 x-tan^2 x) Factorising) =sec...1+tan^2x+tan^x =sec^2x+tan^2x [Sd 1+tan^2x=sec^2x] Therefore,LHS=RHS proved

    4 Answers · Education & Reference · 11/12/2007

  5. LHS = (sec θ - tan θ)(csc θ + 1) = [(1/cos θ) - (sin θ / cos θ)] [(1/sin θ) + 1...

    1 Answers · Education & Reference · 12/07/2011

  6. LHS is -, RHS is + (3x-2) - (5x-2) - (x+1) - x = 4+3+6+2 Now...

    1 Answers · Education & Reference · 11/03/2014

  7. LHS = (ax + b) + (cx + d) First, get rid of the parentheses. ...

    1 Answers · Education & Reference · 18/01/2012

  8. LHS = (cos(x) + 1) / cot(x) = (cos(x) + 1) / (cos(x) / sin(x)) = (sin(x))(cos(x) + 1) / cos...

    1 Answers · Education & Reference · 09/06/2013

  9. LHS = (tanx + cotx)² = tan² x + 2 tanx cotx + cot² x = ...

    2 Answers · Education & Reference · 24/10/2010

  10. LHS = cos² (3x) - cos² (x) => [ ( cos 3x + cos x ) * ( cos 3x - cos x...

    1 Answers · Education & Reference · 21/01/2014

  1. Try asking your question on Yahoo Answers